COVID-19 and review of current recommendations for return to athletic play - Dove, J.; Gage, A.; Kriz, P.; Tabaddor, R. R.; Owens, B. D. (Rhode Island Medical Journal, 2020)
In December 2019 a respiratory illness known as Coronavirus 2 (SARS-CoV-2, COVID-19) broke out in a region in China and rapidly spread to become a pandemic affecting all sporting events worldwide. The Summer Olympics scheduled to be held in Tokyo were postponed until 2021, and all professional leagues in the United States postponed or canceled events. As the United States has begun to open up, there remains uncertainty of when sporting events can safely be held. Many professional leagues and the National Collegiate Athletic Association have established guidelines and recommendations for their athletes to compete safely. In this article, we review the protocols that have been established to allow athletes to return to play, and we review briefly the effects COVID-19 infection may have on athletes.